2020
DOI: 10.3389/fnmol.2020.00088
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Prefrontal Cortex Inhibition in Prepubescent and Adolescent Fragile X Mouse Model

Abstract: Changes in excitation and inhibition are associated with the pathobiology of neurodevelopmental disorders of intellectual disability and autism and are widely described in Fragile X syndrome (FXS). In the prefrontal cortex (PFC), essential for cognitive processing, excitatory connectivity and plasticity are found altered in the FXS mouse model, however, little is known about the state of inhibition. To that end, we investigated GABAergic signaling in the Fragile X Mental Retardation 1 (FMR1) knock out (Fmr1-KO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Overall, the findings of these imaging studies in combination with our detection of decreased GABA in the thalamus supports that FMRP loss affects multiple components of the thalamus, including the GABAergic system. Recent studies have also found that inhibitory deficits in the medial prefrontal cortex in a prepubescent FXS mouse model (Kramvis et al, 2020). Multiple clinical 1 H-MRS studies measuring GABA in various adult populations have found that decreased GABA concentrations in the prefrontal cortex, dorsolateral prefrontal cortex, or frontal cerebrum are correlated with decreased cognitive function and working memory task performance (Yoon et al, 2016;Porges et al, 2017;Kim et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Overall, the findings of these imaging studies in combination with our detection of decreased GABA in the thalamus supports that FMRP loss affects multiple components of the thalamus, including the GABAergic system. Recent studies have also found that inhibitory deficits in the medial prefrontal cortex in a prepubescent FXS mouse model (Kramvis et al, 2020). Multiple clinical 1 H-MRS studies measuring GABA in various adult populations have found that decreased GABA concentrations in the prefrontal cortex, dorsolateral prefrontal cortex, or frontal cerebrum are correlated with decreased cognitive function and working memory task performance (Yoon et al, 2016;Porges et al, 2017;Kim et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Levels of the GABA synthesizing enzyme, glutamic acid decarboxylase, have also been found to be affected in Fmr1 knockout (KO) Drosophila. Lastly, recent studies reveal changes in GABAergic signaling at both pre-and post-synaptic domains of inhibitory synapses in an FXS mouse model (Kramvis et al, 2020). Hence, alterations in GABA A receptor distribution and GABA production and metabolism are pertinent to FXS and make the GABAergic system an attractive path to study.…”
Section: Introductionmentioning
confidence: 99%
“…The quantal amplitude (the mean mIPSC amplitude) is significantly increased as a result of a higher number of postsynaptic GABA A Rs. Although the presynaptic release probability shows no difference between phenotypes, a larger RRP size in FMR1-KO mice attenuates the strength of tetanic depression during high-frequency stimulation [ 48 ]. Together with the above-described changes in glutamatergic transmission, these results favor the suggestion that the observed changes in GABAergic transmission might stabilize the E/I balance in FMR1-KO mice at this age.…”
Section: Fragile X Syndrome (Fxs)mentioning
confidence: 99%
“…The variety of neuropsychiatric symptoms in FXS, such as learning disabilities, hyperactivity, repetitive behaviors, impulsivity, and symptoms affecting social behaviors associated with autism spectrum disorder, suggests dysfunction in multiple brain areas. Cortical [6][7][8][9][10][11][12][13] and hippocampal [14] dysfunctions have been extensively studied. Although the symptomology of FXS includes social deficits [15] compatible with altered neuronal functions in the mesolimbic network and the basal ganglia [16,17], studies addressing how FXS modifies neuronal excitability in these systems are scarce.…”
Section: Introductionmentioning
confidence: 99%